2008
DOI: 10.1007/s12253-008-9082-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of EGFR Gene Amplification, Protein Over-expression and Tyrosine Kinase Domain Mutation in Recurrent Glioblastoma

Abstract: Gefitinib and erlotinib are both selective EGFR tyrosine kinase inhibitors (EGFR-TKIs) that have produced responses in a small subgroup of lung cancer patients. The strongest evidence for a role of EGFR in the biology of glioblastoma stems from clinical trials in which 15-20% of recurrent glioblastoma patients experienced significant tumour regression in response to these small-molecule EGFR kinase inhibitors. We examined the protein-kinase domain of the EGFR gene, EGFR protein expression and EGFR gene amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…[35][36][37] Data on the effect of reirradiation, applied as normofractionated or hypofractionated stereotactic small volume radiotherapy are limited regarding further tumor growth, but it may aggravate neurological toxicity. [38][39][40][41][42][43][44][45][46][47] In long-term survivors, there are concerns regarding radiation-induced late sequelae, in particular delayed leukoencephalopathy with neurocognitive dysfunction or radiation necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Data on the effect of reirradiation, applied as normofractionated or hypofractionated stereotactic small volume radiotherapy are limited regarding further tumor growth, but it may aggravate neurological toxicity. [38][39][40][41][42][43][44][45][46][47] In long-term survivors, there are concerns regarding radiation-induced late sequelae, in particular delayed leukoencephalopathy with neurocognitive dysfunction or radiation necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, various exon deletion mutations including exon 25–27 and exon 25–28 deletion mutations, which result in the truncation of the C-terminal domain of EGFR, have been identified in GBM patients although their oncogenic potential has not yet been characterized (17, 18). Furthermore, EGFR gene amplification and/or EGFR protein overexpression commonly occur in approximately 50% of GBM patients, suggesting that an increased abundance of the EGFR may also be responsible for tumorigenesis in primary GBM (7, 19). Interestingly, somatic mutations within the EGFR kinase domain, which are frequently identified in non-small cell lung cancer, have only rarely been identified in GBM (8, 14, 20).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have identified epidermal growth factor receptor as a common genetically altered gene in primary GBM [35-37], by: i) amplifications [35, 38] ii) exon deletions affecting either the extracellular, either cytoplasmatic domain [39-41] iii) point mutations within the extracellular domain of EGFR [42]. These genetic alterations have been shown to lead to oncogenic activation of the mutant receptor independent of ligand stimulation and, consequently, induce cellular transformation.…”
Section: Targeting Egfr and Pi-3k/akt/mtor Pathwaymentioning
confidence: 99%